Scapular kinematic reconstruction – segmental optimization, multibody optimization with open-loop or closed-loop chains: which one should be preferred?. Issue 2 (3rd November 2017) - Michaud, Benjamin; Duprey, Sonia; Begon, Mickaël
Abstract: Several numerical approaches have been developed to address the soft tissue artefact, such as the segmental optimization and multibody kinematics optimizations using either open-loop or closed-loop chains. However, it is still not clear which method is the most efficient for scapular kinematics reconstruction. In this study, six kinematic models were compared to a silver standard, i.e. a scapula palpator, during a series of 55 postures with maximal amplitudes of both the arm and scapula performed by 15 subjects. The most accurate approaches were the multibody optimization with a closed-loop chain and the segmental optimization. They provided averaged scapula misorientations of 14.9 ± 6.7° and 16 ± 7.1, respectively. Regarding the closed-loop chain integrating a point-to-ellipsoid scapulothoracic joint, the ellipsoid providing the most accurate results was a thorax-size ellipsoid fitting the area browsed by the scapula. Eventually, considering the high implementation costs of a multibody kinematics optimization, the segmental optimization could be considered as appropriate for scapular kinematics reconstruction.